Geochronology and Geochemistry of Calcite-Filled Fractures, Southern Ontario: Insight Into Cretaceous Deformation - Spalding, Jennifer (Université d'Ottawa / University of Ottawa, 2018)
The St. Lawrence Platform is located along the northern shoreline of Lake Ontario, currently in an intra-cratonic setting exposing relatively flat-lying middle Ordovician sedimentary strata. The purpose of this study is to gain insight on recent brittle deformation events that have deformed the bedrock. Based on structural field observations, broadly trending E-W extensional joints are the youngest stress recorded in the bedrock. These joints are partially filled and sealed with calcite mineralization and were strategically sampled to gain insight on the source and timing of fluid flow. Trace element geochemistry and stable isotope (δ18O and δ13C) analysis on calcite mineralization indicate that their compositions are analogous to the host rock, thus, fluids originate from connate fluids that were released from pore space during deformation. In addition, U-Pb geochronology via LA-ICP-MS methods yield a model age of 101 ± 6 Ma (MSWD: 2.3). The date of calcite crystallization is contemporaneous with the establishment of North America’s modern compressive stress field, and is linked to a Cretaceous tectonic plate reorganization event that was global in scale. This study demonstrates that calcite veins can serve as a tool to date brittle deformation in limestone, which could have direct applications in hydrocarbon exploration, paleohydrology, and the consideration for locating sites to host deep geological repositories.
Keywords: Geochronology; Geochemistry; Cretaceous deformation; Calcite veins